Explaining Administrative Service Performance: The Roles of Leadership, Organizational Culture, Technology, and Human Resource Management - Zainal Abidin Rengifurwarin (Universitas Pattimura, 2026)
Despite extensive reforms in public administration, substantial variations in administrative service performance persist among local government organizations operating under similar regulatory frameworks. This study examines how organizational capacities explain these variations by investigating the roles of leadership, organizational culture, technology, and human resource management in shaping administrative service performance. An intrinsic qualitative case study was conducted at the Dullah Utara Subdistrict Office, Tual City, Indonesia. Data were collected through in-depth interviews, non-participant observation, and document analysis involving ten purposively selected informants comprising government officials, administrative staff, and service users. Thematic analysis was employed to identify patterns linking organizational capacities with service performance. The findings reveal that administrative service performance is manifested through transparency, reliability, responsiveness, accountability, effectiveness, and efficiency. These dimensions are collectively reinforced by four interrelated organizational capacities: strategic leadership, a service-oriented organizational culture, technological support for administrative processes, and human resource management that enhances employee competence and service consistency. Conversely, inadequate human resource development and limited technological infrastructure constrain service continuity and organizational effectiveness. The study demonstrates that administrative service performance is better understood as an organizational capability emerging from the integration of complementary institutional capacities rather than mere compliance with administrative procedures. This integrative perspective extends organizational capacity theory within public administration and offers practical insights for strengthening administrative governance in small-island local government settings.